Teaching What Society Needs: "Hacking" an Introductory Marketing Course With Sustainability and Macromarketing. (December 2022) - Watson, Forrest; Stanton, Julie; Beninger, Stefanie; Domegan, Christine; Reppel, Alexander; Shapiro, Stanley
Marketing classes are often focused on the micro level, failing to account for wider societal issues. In this article, we argue for the inclusion of a wider macro-sustainability focus, one that "hacks" marketing education. With that objective in mind, we developed and delivered an introductory marketing course that integrated both the micro and the macro, thus infusing the course with macro-sustainability. This was done through an "expanded voice" perspective that included alternate complementary micro and macro class sessions while using a traditional managerial marketing textbook supplemented by macro-sustainability materials. We also integrated a controversies approach to support discussion and learning. We taught this course to 150 undergraduate students and conducted both quantitative and qualitative assessments of the course, including comparing results with an "unhacked" marketing course. Findings indicated increased awareness of macro-sustainability topics and movement on appreciation of sustainability and the role marketing can have in achieving this awareness. Finally, we offer a model of how marketing classes at all levels can be "hacked" with a macro-sustainability approach.